2020
DOI: 10.1177/0887403420980823
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Probation Officer Tasks by Officer-Caseload Type

Abstract: Prior research regarding probation officer roles and tasks has included statutory analyses, time studies, and computation of daily tasks in relation to risk level of offenders. However, there is limited research investigating specific proportions of probation officer tasks by officer caseload type. The current study builds on existing literature by providing an initial investigation into the daily tasks of adult probation officers of a medium-sized, tri-county probation department in a Southwestern state. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…We purposely targeted samples released from custody as they tend to be more persistent in their criminality, have committed offences of a more serious nature, and have higher rates of recidivism (Ministry of Justice, 2020). Arguably therefore, and in the context of the increased workload demands within Probation Services (DeMichelle & Payne, 2018;Martin & Zettler, 2020), there is urgency in identifying those at higher risk of recidivism among samples pending custodial release. We also focused on a defined follow-up period of six months to four years on the basis that, in those countries that measure recidivism over five years or more, the trajectory of recidivism is steepest up to six months and tails off significantly after three years (Durose et al, 2014;Fazel & Wolf, 2015).…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…We purposely targeted samples released from custody as they tend to be more persistent in their criminality, have committed offences of a more serious nature, and have higher rates of recidivism (Ministry of Justice, 2020). Arguably therefore, and in the context of the increased workload demands within Probation Services (DeMichelle & Payne, 2018;Martin & Zettler, 2020), there is urgency in identifying those at higher risk of recidivism among samples pending custodial release. We also focused on a defined follow-up period of six months to four years on the basis that, in those countries that measure recidivism over five years or more, the trajectory of recidivism is steepest up to six months and tails off significantly after three years (Durose et al, 2014;Fazel & Wolf, 2015).…”
Section: The Current Studymentioning
confidence: 99%
“…Moreover, on release to the community, criminal justice professionals often have to distinguish these individuals quickly -to direct finite resources to the management of those at highest risk of causing harm. These decisions are made in the context of increasing workload demands (DeMichelle & Payne, 2018;Martin & Zettler, 2020); for example over the past 30 years the number of people sentenced to indeterminate sentences has increased three-fold both in the US (The Sentencing Project, 2020) and in the UK (MoJ, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For some POs, navigating the pandemic brought forth negative experiences. Martin and Zettler (2021) found that 30% of POs in their study were overwhelmed during the pandemic. Officers were forced to navigate adjustments to their typical approach to the job, while also managing the increased needs of clients (e.g., increased mental health concerns, employment, housing, and food insecurity) (Schwalbe & Koetzle, 2021).…”
Section: Officer-level Changes Due To Covid-19mentioning
confidence: 88%